Paradise lost: The costs of state failure in the Pacific - Lisa Chauvet; Paul Collier; Anke Hoeffler (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Globally, state failure is hugely costly. We estimate the total cost of failing states at around US276 billion per year. In this paper we apply our global framework and methodology to analyse the cost of failing states in the Pacific Ocean. Globally, failing states inflict very large costs on their neighbours and this both justifies and requires regional intervention in decision processes that would normally be the sovereign domain of nation states. Our analysis suggests that islands do not have neighbours in this economic sense. In this respect the Pacific region is distinctive, because its countries are islands, the neighbourhood spillovers that normally generate these costs do not apply. Due to the lack of spillovers we estimate the cost of state failure at US36 billion. However, our results also indicate that failing states themselves suffer considerably more in terms of income losses if they are islands. This may be due to the greater openness of islands, implying greater flight of financial and human capital. We conclude that because neighbours are not directly affected by state failure in the Pacific, any possible interventions should be centred on the humanitarian concern rather than be guided by self-interest of the other countries within the Pacific region.
Keywords: F5; H56; O56; 330; Pacific islands; governance; costs; growth; civil war; Staatsversagen; Insel; Pazifischer Raum